Early Childhood Predictors of the Social Competence of Adults with Autism. - Gillespie-Lynch, Kristen; Sepeta, Leigh; Wang, Yueyan; Marshall, Stephanie; Gomez, Lovella; Sigman, Marian; Hutman, Ted (Journal of Autism & Developmental Disorders, 2012)
Longitudinal research into adult outcomes in autism remains limited. Unlike previous longitudinal examinations of adult outcome in autism, the twenty participants in this study were evaluated across multiple assessments between early childhood (M = 3.9 years) and adulthood (M = 26.6 years). In early childhood, responsiveness to joint attention (RJA), language, and intelligence were assessed. In adulthood, the parents of participants responded to interviews assessing the adaptive functioning, autistic symptomology and global functioning of their children. RJA and early childhood language predicted a composite measure of adult social functioning and independence. Early childhood language skills and intelligence predicted adult adaptive behaviors. RJA predicted adult non-verbal communication, social skills and symptoms. Adaptive behaviors changed with development, but symptoms of autism did not. Additional factors associated with adult outcomes are discussed.